1989
DOI: 10.3758/bf03199556
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intraword and interword letter repetition: A test of the word unitization hypothesis

Abstract: Do words, as familiar units or gestalts, tend to swallow up and conceal their letter components (Pillsbury, 1897)? Letters typically are detected faster and more accurately in words than in nonwords (i.e., scrambled collections of letters), and in more frequent words than in less frequent words. However, a word advantage at encoding, where the representation of the string is formed, might compensate for, and thus mask, a word disadvantage at decoding and comparison, where the component letters of the represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 31 publications
2
30
1
Order By: Relevance
“…For accuracy, these effects were not analogous to word superiority effects, which occur only with certain masking stimuli (e.g., Johnston & McClelland, 1980) or other stimulus degrading procedures, such as luminance reduction or direct feature removal (Marchetti & Mewhort, 1986). For latency, the whole advantage may be more analogous to findings in the word superiority paradigm, since word superiority for RTs has been found without masking (e.g., Johnson, 1975;Krueger, 1970Krueger, , 1989Polf, 1976). A comparison with object superiority effects is more ambiguous because, although object superiority effects occur without masking, they do not occur with RT measures (Klein, 1978).…”
Section: Discussionmentioning
confidence: 88%
“…For accuracy, these effects were not analogous to word superiority effects, which occur only with certain masking stimuli (e.g., Johnston & McClelland, 1980) or other stimulus degrading procedures, such as luminance reduction or direct feature removal (Marchetti & Mewhort, 1986). For latency, the whole advantage may be more analogous to findings in the word superiority paradigm, since word superiority for RTs has been found without masking (e.g., Johnson, 1975;Krueger, 1970Krueger, , 1989Polf, 1976). A comparison with object superiority effects is more ambiguous because, although object superiority effects occur without masking, they do not occur with RT measures (Klein, 1978).…”
Section: Discussionmentioning
confidence: 88%
“…The response here is based on the physical similarity between the two arrays. Using this procedure, Kreuger (1989) showed that subjects were faster when the pairs were words than when the pairs were non-words. This was taken to indicate that the task involved lexical access to some degree.…”
Section: The Perception Of Printed Words: the Same-different Taskmentioning
confidence: 98%
“…This would predict that when one reads a word one is as conscious of the word as of each of its constituent letters. Empirical evidence supporting the unitization hypothesis of lexical and alphabetic recognition suggests otherwise (e.g., Krueger, 1989;Greenberg, 1988). In fact, in a simple reading task we are much more conscious of the meaning of a word than the letters in its spelling, unless we are specifically directed to pay attention to the latter.…”
Section: The Delay Problem For the Onset Of Conscious Experiencementioning
confidence: 99%